Pengaruh Pencucian Kompresor terhadap putaran Poros Pada Mesin Turbofan - Abubakar As’siddiq; Mukhammad Yusuf Hakim; Reza Fadilah Romadloni (Universitas Muhammadiyah Tangerang, 2026)
This study quantifies the influence of on-wing compressor washing on turbofan engine performance retention and deterioration rate, with the objective of identifying an optimal wash interval that maximizes fuel efficiency and supports life-limited hardware management. An analytical, data-driven method was applied using Aircraft Communications Addressing and Reporting System (ACARS) snapshots to track post-wash performance trends over successive block cycles. Changes in cruise fuel-flow characteristics and exhaust gas temperature margin (TGT/EGT margin) were used as primary indicators of efficiency recovery and subsequent degradation. Results show a measurable post-wash performance recovery, including an average improvement in cruise delta fuel flow and a corresponding increase in temperature margin of approximately 0.6 °C, consistent with reduced compressor fouling losses. Trend analysis of margin deterioration normalized per 100 cycles indicates a steeper inefficiency growth rate during the first 200 cycles after washing, followed by a slower degradation rate thereafter. Based on the observed two-slope deterioration behavior, the findings support scheduling compressor washes at approximately 200–250 cycles to capture the highest marginal efficiency benefit while contributing to sustained operability and longer on-wing time.